2009
DOI: 10.1186/1471-2458-9-291
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of risk factors for non-communicable diseases in the Mekong Delta, Vietnam: results from a STEPS survey

Abstract: BackgroundDespite the increasing burden of non-communicable diseases (NCD) in Vietnam, information on the prevalence of preventable risk factors for NCD is restricted to the main urban centres of Ha Noi, and Ho Chi Minh City (HCMC). This population-based survey aimed to describe the prevalence of risk factors for NCD in a rural Vietnamese sample.MethodsThis survey was conducted using the WHO "STEPwise approach to surveillance of non-communicable diseases" (STEPS) methodology. Participants (n = 1978) were resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
5
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 13 publications
7
34
5
1
Order By: Relevance
“…Of those with hypertension, only 32.3% had prior knowledge of their condition, and less than half of these were on treatment. 7 Prevalence of physical inactivity among the respondents in this study was 54.30% which was lower than that of the Ghana STEPS Survey (76.7%) and higher than similar study conducted in Vietnam with 34.71% 11 and rural area of Kerala, India with 9.5%. 10 The prevalence of obesity, which is a potentially modifiable risk factor for non-communicable diseases 15 in the study was 40.4%, which was greater than 14.1% in a study in rural and urban Accra 4 and 5.5% among Ghanaians 16 as well as 9% in the GDHS.…”
Section: Introductioncontrasting
confidence: 81%
“…Of those with hypertension, only 32.3% had prior knowledge of their condition, and less than half of these were on treatment. 7 Prevalence of physical inactivity among the respondents in this study was 54.30% which was lower than that of the Ghana STEPS Survey (76.7%) and higher than similar study conducted in Vietnam with 34.71% 11 and rural area of Kerala, India with 9.5%. 10 The prevalence of obesity, which is a potentially modifiable risk factor for non-communicable diseases 15 in the study was 40.4%, which was greater than 14.1% in a study in rural and urban Accra 4 and 5.5% among Ghanaians 16 as well as 9% in the GDHS.…”
Section: Introductioncontrasting
confidence: 81%
“…The prevalence of smoking in this sample has been presented elsewhere [22]. The proportions of current smokers, ex-smokers, and never-smokers were 67.8 (631/910), 13.0 (130/910), and 19.2% (149/910), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Eligible participants for this survey were selected by multistage sampling with age, sex, and urban/rural stratification. Details about the survey have been published elsewhere [22]. Informed consent was obtained from participants.…”
Section: Participantsmentioning
confidence: 99%
“…In Vietnam, these issues have been investigated in a few published studies. [3][4][5][6] Mirroring reasonably well the results of studies in Western countries, predictors of elevated BP identified in these studies include increasing age, male sex, tobacco smoking and alcohol consumption, indicators of overweight or body fatness, markers of low socioeconomic status including education and occupation, and marital status.…”
Section: Introductionmentioning
confidence: 89%
“…6,13 Both surveys had approximately equal numbers of participants within four age categories (25-34, 35-44, 45-54 and 55-64 years). In BTH, participants were selected by age-and sex-stratified random sampling from among those on the Electoral Roll of registered voters in Tasmania who had an address within the Burnie municipalities.…”
Section: Study Populationmentioning
confidence: 99%